Demographic features, BMPR2 status and outcomes in distal chronic thromboembolic pulmonary hypertension. Issue 7 (7th February 2007) - Suntharalingam, Jay; Machado, Rajiv D; Sharples, Linda D; Toshner, Mark R; Sheares, Karen K; Hughes, Rodney J; Jenkins, David P; Trembath, Richard C; Morrell, Nicholas W; Pepke-Zaba, Joanna
Abstract : Background: Although pulmonary endarterectomy (PEA) is potentially curative in chronic thromboembolic pulmonary hypertension (CTEPH), some patients have distally distributed disease that is not amenable to surgery. The aetiology and characteristics of this patient group are currently not well understood. Objectives: This study compares the baseline demographic features and outcomes in subjects with distal CTEPH, those with proximal CTEPH and those with idiopathic pulmonary arterial hypertension (IPAH) to determine whether these conditions represent separate entities or whether they exist along the same spectrum of disease. Methods: The medical history, clinical characteristics, bone morphogenetic protein receptor type II (BMPR2) mutation status and outcomes of 96 subjects with IPAH, 35 with distal CTEPH and 68 with proximal CTEPH referred to a single specialist centre between 1994 and 2005 were reviewed. Results: There were significant differences between the distal CTEPH, proximal CTEPH and IPAH groups in age (55.9 years vs 54.8 years vs 46.2 years, p<0.001), proportion who were male (43% vs 69% vs 29%, p<0.001), previous deep vein thrombosis (28.6% vs 30.9% vs 3.1%, p<0.001), positive BMPR2 status (0% vs 0% vs 15%, p = 0.018), mean pulmonary artery pressure (47.3 mm Hg vs 45.4 mm Hg vs 54.8 mm Hg, p<0.001) and total pulmonary resistance (12.9 WU vs 12.4 WU vs 18.1 WU, p<0.001). Patients with distal CTEPH and those with IPAH were managed similarly and had comparable survival characteristics (1 year survival 77% vs 86%; 3 year survival 53% vs 60%; p = 0.68). Conclusions: Patients with distal CTEPH share certain demographic features with patients with proximal CTEPH that not only indicate a common aetiology but also help to differentiate them from patients with IPAH. Despite more favourable haemodynamic parameters in those with distal CTEPH, patients in this group had a poor long-term outcome which was similar to that of patients with IPAH.